Accumulation of fibrosis and altered perifollicular stromal differentiation in vitrified‐thawed human ovarian tissue xenografted to nude mice. (10th March 2022) - Kitajima, Michio; Murakami, Naoko; Kitajima, Yuriko; Kajimura, Itsuki; Matsumura, Asako; Matsumoto, Kanako; Harada, Ayumi; Miura, Kiyonori
Abstract: Purpose: Ovarian tissue cryopreservation and its auto‐transplantation is promising technique in fertility preservation. Longevity of grafted tissue is limited though mechanism of follicle reduction is not fully understood. We evaluated histological alteration of vitrified‐thawed ovarian tissue that grafted to nude mice. Materials and Methods: Human ovarian tissue was cryopreserved by vitrification. After thawing, they were grafted to mesentery of nude mice. Twelve weeks after transplantation, the implants were removed and histologically examined. The presence of follicles, the degree of fibrosis, and TUNEL staining in surrounding cortex were evaluated. The stromal expressions of alpha‐smooth muscle actin (aSMA) were determined. Results: Normal ovarian cortex was decreased, and fibrotic area were significantly increased after grafting. The distributions of developmental stage of follicles shifted toward activation of follicular growth. Stromal TUNEL staining was increased in frozen/thawed tissue. The expression of aSMA were found in perifollicular stroma of growing follicles, which were decreased in grafted tissue associated with reduction of cortical stroma. Conclusions: Fibrosis, reduced cortical stroma, and activation of dormant follicles were concomitantly observed in grafted ovarian cortex, which may relate to limited longevity. Perifollicular aSMA expression can be regarded as a marker of the competence of cortical stroma that regulate follicular development. Abstract : Auto‐transplantation of cryopreserved human ovarian tissue is promising technique but longevity of grafted tissue is limited. We demonstrated massive fibrosis, reduction of normal cortical stroma, activated follicular growth and altered differentiation of perifollicular stromal cell by xenografting nude mice model. These histological features may be related to the diminished ovarian reserve in grafted ovarian tissue.